William Faulkner : from Jefferson to the world - Waggoner, Hyatt Howe (University of Kentucky Press, 1959)
Combining explications of William Faulkner's novels and short stories with thematic analysis, Hyatt H. Waggoner works from the close reading of a specific work outward to its most general meanings and relationships. By this method he has made a significant contribution to the understanding of Faulkner's career and artistic achievement. Waggoner examines both better and lesser-known works, which yield valuable insights into Faulkner's development when treated in relation to his whole body of work. The author also addresses the major themes which emerge from critical analyses of individual works.